CLINICAL STUDY TO EVALUATE THE EFFICACY OF PUNARNAVA CHURNA ON VYANA BALA VAISHAMYA (HYPERTENSION) - Ghuraiya, *Shyamveer; Mandal, Sisir Kumar (International Journal of Ayurveda and Pharma Research, 2018)
In essential hypertension, mainly Vata prakopa occurs, particularly Vyana vata as it is responsible for Rasa- rakta samvahana. By virtue of its Ruksha, Sheeta and Khara guna, Rasa-rakta vahini dhamanis are constricted, also its Ruksha guna dries the Malarupa kapha at the inner side of the vessels making them more rigid (Kathin). Vascular lumen may be reduced further leading to obstruction in it. So, for normal circulatory function, increased force of Vyana vayu is required resulting into Vyana bala Vaishamya and hence leading to the development of hypertension. The WHO rates hypertension as one of the most important causes of premature death worldwide. Worldwide, approximately 1 billion people have hypertension, contributing to more than 7.1 million deaths per year. The number of adults with hypertension in 2025 is predicted to increase by about 60% to a total of around 1.56 billion. In India, Cardiovascular diseases caused 2.3 million deaths in the year 1990; this is projected to double by the year 2020. Numbers of drugs are available in modern medicine to treat the disease in its symptomatically active state but still are unable to cure the hypertension. Hyper function of Vyana is considered under Vyana Bala Vaishamya which produces increased force in the wall of the channels (blood vessels) to produce the disease hypertension. In the present clinical trial ‘Punarnava Churna’ is orally administered for 1 month twice a day after food. 30 clinically diagnosed patients of hypertension were randomly selected and divided into two groups. BP, CBC, RBS, ECG, Blood urea, Serum creatinine and Lipid profile were done before and after the clinical trial. After completion of study signs and symptoms were controlled significantly and also there were significant changes in laboratory findings.